2008
DOI: 10.4103/0255-0857.43583
|View full text |Cite
|
Sign up to set email alerts
|

High rate of mutation K103N causing resistance to nevirapine in Indian children with acquired immunodeficiency syndrome

Abstract: In north India the number of paediatric cases with acquired immunodeÞ ciency syndrome (AIDS) is on the rise. Most drug combinations used for treatment of AIDS incorporate nevirapine, resistance to which develops very fast if given singly or because of unplanned interruptions. This paper investigates presence of mutations at codon 103 and codon 215 of the HIV pol gene causing resistance to nevirapine and zidovudine (AZT) respectively in 25 children with AIDS. Mutations T215Y and K103N were detected by a nested … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 7 publications
0
7
0
Order By: Relevance
“…Other paediatric studies from India have revealed similar low TDRM prevalence; among a south Indian cohort of 48 perinatally infected children of mean age 5.7 years, none had major drug resistance mutations [27]. In another study from north India where 25 ART-naïve children with mean age 6 years were studied, K103N was the only drug resistance mutation that was observed [28]. Studies on ART-naïve adults from different parts of India with sample sizes ranging from 34 to 107 patients, have revealed low TDRM prevalence (<5%) [11,12,14-18].…”
Section: Discussionmentioning
confidence: 84%
“…Other paediatric studies from India have revealed similar low TDRM prevalence; among a south Indian cohort of 48 perinatally infected children of mean age 5.7 years, none had major drug resistance mutations [27]. In another study from north India where 25 ART-naïve children with mean age 6 years were studied, K103N was the only drug resistance mutation that was observed [28]. Studies on ART-naïve adults from different parts of India with sample sizes ranging from 34 to 107 patients, have revealed low TDRM prevalence (<5%) [11,12,14-18].…”
Section: Discussionmentioning
confidence: 84%
“…In Thailand, a duplex ARMS-PCR assay was successfully applied to detect K103N/Y181C and Q151M/ T215Y mutations in 45 naive and treated HIV-1 CRF01_AE-infected patients that achieved good performance ratings (96% sensitivity and 98% specificity) similar to those of Sanger sequencing (60). The suitability of ARMS-PCR was also demonstrated in two studies carried out in India that screened 60 individuals for mutations at codons 70, 184, and 215 (43) and 25 children for mutations at codons 103 and 215 (44). The good performance of ARMS-PCR comes with a fast turnaround time and low cost but has the limitation of providing information on only select mutations.…”
Section: Figmentioning
confidence: 99%
“…They have been developed as an alternative for genotyping assays, among which amplification-refractory mutation system (ARMS)-PCR uses the difference in extension efficiency between primers with matched and mismatched 3= bases to identify mutations based solely on the presence of PCR products via gel electrophoresis. ARMS-PCR was developed in 1989 and was further optimized by our group and others to identify HIVDR mutations with high performance compared to that of standard sequencing (39)(40)(41)(42)(43)(44). So far, no study has compared point mutation assays with NGS.…”
mentioning
confidence: 99%
“…In India, studies of drug resistance have identified a maximum frequency of 81% among treated patients [8,9] and 56% among the paediatric population [10], although these studies had small sample sizes and identified resistance at virological failure that does not reflect the current scenario. Here, we present the frequency and pattern of resistance mutations to reverse transcriptase (RT) inhibitors among patients receiving first-line treatment who developed confirmed immunological failure (IF).…”
Section: Introductionmentioning
confidence: 99%